Precise Point Positioning with GNSS Raw Measurements from an Android Smartphone in Marine Environment Monitoring. Issue 3 (4th May 2022) - Tunalioglu, Nursu; Ocalan, Taylan; Dogan, Ali Hasan
Abstract: In the next generation, the use of dual-frequency Embedded GNSS Chipset in the smart devices, which will be widely used in engineering applications, has been used for the first time in Xiaomi Mi8. Considering this development dynamics, a kinematic test was carried out in the marine environment monitoring with a geodetic GNSS receiver and an android smartphone in Turkey Oyak Port. According to the results of the test, RMSE for horizontal coordinate components were found as 0.0423 m and 5.9493 m for reference solution and PPP-AR solution of geodetic receiver, and reference solution and PPP solution of smartphone, respectively. Moreover, the positional errors of individual epochs were computed as 0.0411 m and 4.6871 m with respect to given order. The solution obtained from Xiaomi Mi8 raw GNSS data with PPP approach provides the Order 2 for hydrographic survey standards IHO S-44 in terms of Total Horizontal Uncertainty (THU).